Exploring Experiences of Psychiatric Nursing Simulations Using Standardized Patients for Undergraduate Students - Yun-Jung Choi, PhD, RN, PMHNP (Elsevier, 2012)
Purpose: This study was conducted to explore and understand the experiences of nursing students related to psychiatric simulation using standardized patients and to identify the value of such simulations in relation to the psychiatric clinical practicum. Methods: This study was designed using qualitative research. Eleven undergraduate students were individually interviewed regarding their experiences with psychiatric nursing simulation. A thematic content analysis was conducted to derive themes from subthemes, which were derived from contents of the interview. Results: Four themes were derived from nine subthemes by means of thematic analysis of nursing students' experiences regarding psychiatric nursing simulation with standardized patients compared to clinical psychiatric nursing practicum. The topics studied included gaining practice without fear, gaining confidence in clinical practicum, being embarrassed by the gap and being in need of further simulation. Conclusion: Exploration of student responses comparing simulation and clinical practicum enhances integration of dichotomous experiences that bridge the theory-practice gap, which magnifies the benefits of the simulation.